Cerebral oxygenation during submaximal and peak exercise for sedentary adults with and without down syndrome - Boer, Pieter-Henk (Frontiers in Physiology, 2025)
BackgroundIndividuals with Down syndrome (DS) are born with or develop many physical limitations which affect their quality of life. Although studies involving cerebral oxygenation in the general population have been performed, such a study is yet to be conducted on individuals with DS.MethodFifty-four participants (DS:27; non-DS:27) were tested for cerebral oxygenation during an incremental exercise test. Participants (38.9 ± 5.9 years) were tested for ΔHbO2 and ΔHHb using near-infrared spectroscopy. V̇O2 peak determination was performed with a standardised incremental treadmill protocol and the ventilatory threshold (VT) and respiratory compensation point (RCP) were determined.ResultsThere were no significant differences for V˙O2 between 80%VT, VT, RCP and V˙O2 peak, as well as VT/ V˙O2 peak and RCP/ V˙O2 peak between DS and non-DS groups (p > 0.05). Significant differences between DS and non-DS were reported for ΔHbO2 in the left and right prefrontal cortex for both males and females (p < 0.05) with medium to large effect sizes, but not for ΔHHb (p > 0.05) (except for males regarding RPC). Significant main effects over exercise intensity for ΔHbO2 and ΔHHb were noted for both groups, genders and hemispheres, but differences with respect to the ΔHHb in transition from RCP to peak exercise.ConclusionA significant different evolution for ΔHbO2 over exercise intensity (80% VT, VT, RCP, VO2 peak) between sedentary adults with and without DS was found. This ΔHbO2 may possibly reflect previously reported executive function limitations and/or the many physiological limitations that individuals with DS are born with or develop over time. Such speculations would need to be tested with future cause-effect studies.